2005
DOI: 10.1002/anie.200502781
|View full text |Cite
|
Sign up to set email alerts
|

Smooth Anodic TiO2 Nanotubes

Abstract: In 1999 Zwilling et al. reported on the electrochemical formation of self-assembled TiO 2 nanotubes (p-TiO 2 ) by the anodization of Ti, [1] and other reports followed soon thereafter. [2,3] A factor limiting the application of this first generation of nanotubes was their production in hydrofluoric acid based electrolytes. As a result of the high rate of chemical dissolution of TiO 2 in these solutions, the nanotubes could be grown only up to a length of 500 nm. Recently, we have shown [4][5][6][7] and explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

32
1,012
3
23

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,071 publications
(1,070 citation statements)
references
References 21 publications
32
1,012
3
23
Order By: Relevance
“…We assume that CuCl 2 /HCl solution weakens further the junction strength between cells by chemically dissolving oxide material at the cell boundaries. This assumption is somewhat in line with the recent experimental observation by Zhao et al, who reported that triple junction points in AAO membrane formed by high current density (j ) 160 mA/cm 2 ) anodization can preferentially be etched by aqueous CuCl 2 /HCl solution due to the presence of some hydrated aluminum oxide (e.g., Al(OH) 3 or AlOOH) at the triple cell junction sites. 24 SEM micrographs of alumina nanotubes formed at different HA-pulse durations are shown in Figure 2b,e, demonstrating convenient and reliable control over the length of alumina nanotubes by varying the pulse duration of HA (i.e., τ HA ).…”
supporting
confidence: 89%
“…We assume that CuCl 2 /HCl solution weakens further the junction strength between cells by chemically dissolving oxide material at the cell boundaries. This assumption is somewhat in line with the recent experimental observation by Zhao et al, who reported that triple junction points in AAO membrane formed by high current density (j ) 160 mA/cm 2 ) anodization can preferentially be etched by aqueous CuCl 2 /HCl solution due to the presence of some hydrated aluminum oxide (e.g., Al(OH) 3 or AlOOH) at the triple cell junction sites. 24 SEM micrographs of alumina nanotubes formed at different HA-pulse durations are shown in Figure 2b,e, demonstrating convenient and reliable control over the length of alumina nanotubes by varying the pulse duration of HA (i.e., τ HA ).…”
supporting
confidence: 89%
“…9 The results from Schmuki indicate that the TONT array length can be increased up to 7 µm when the pH of the anodization electrolyte is kept high while remaining acidic. 10 In 2006, Grimes reported a new generation of vertically oriented TiO 2 nanotubes with length up to 134 µm by using various non-aqueous electrolytes. 11 In our previous work, a TONT array was grown on the surface of a titanium substrate by the anodization technique.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] This method offers suitably back-contacted nanotube layers on the substrate, which can be employed directly as an electrochemical device or a probe. [2][3][4]12 Recently, self-organized titania nanotubes have been used as supercapacitor electrode material as an alternative to or co-material with other metal oxides, due to their semiconducting properties, accessible surface, electrochemical behaviour and long-term chemical stability. [13][14][15][16] It is widely believed that bare titania due to high electric resistance and low specific surface area reveals low electrochemical capacitance.…”
mentioning
confidence: 99%
“…Common to almost all anodic approaches, the side walls of the tubes exhibited irregularities, resulting in some moderate thickness variations (ripples), which is typical of low viscosity electrolytes containing glycerol. 15,19 This thin sheet of nanotubes can potentially act simultaneously as both an active material and a current collector. Fig.…”
mentioning
confidence: 99%